Menguji Dampak Profitabilitas dan Firm Size Terhadap Penghindaran Pajak Selama Pandemi Covid-19 Pada Perusahaan Kategori Hotel, Restoran dan Pariwisata - Dian Maulita; Lulu Nailufaroh (Jurnal Manajemen, 2022)
Toward the start of 2020, practically all nations were stunned by the episode of the Covid pandemic. Because of the appearance of the Covid disease, the public authority had to force another guideline, in particular friendly separating or known as PSBB. This new strategy significantly affects the decrease in financial advancement. In this way pay in the travel industry area is diminished. Organization proprietors will likewise for the most part encourage chiefs to stay away from charge by stifling duty development. The reason for this examination is to look at the components that affect charge evasion during the Covid pandemic in organizations that are remembered for the arrangement of the travel industry, café and inn industry in the first, second, and third quarters of 2020. The populace in this study are organizations in the inn, eatery and the travel industry class. recorded on the Indonesia Stock Exchange in the period 2020. Purposive examining was picked as the testing method in this review. The investigation utilized for information handling is numerous direct relapse. This examination infers that there is an adverse consequence of profitability on tax avoidance and an adverse consequence of firm size on tax avoidance Keyword : Profitability; Firm Size; Tax Avoidance